Comparative analysis of monoclonal antibodies against prostate‐specific membrane antigen (PSMA). Issue 16 (27th September 2014) - Tykvart, J.; Navrátil, V.; Sedlák, F.; Corey, E.; Colombatti, M.; Fracasso, G.; Koukolík, F.; Bařinka, C.; Šácha, P.; Konvalinka, J.
<x xml:space="preserve">Abstract</x> BACKGROUND Prostate‐specific membrane antigen (PSMA), also known as glutamate carboxypeptidase II (GCPII), is generally recognized as a diagnostic and therapeutic cancer antigen and a molecular address for targeted imaging and drug delivery studies. Due to its significance in cancer research, numerous monoclonal antibodies (mAbs) against GCPII have been described and marketed in the past decades. Unfortunately, some of these mAbs are poorly characterized, which might lead to their inappropriate use and misinterpretation of the acquired results. METHODS We collected the 13 most frequently used mAbs against GCPII and quantitatively characterized their binding to GCPII by enzyme‐linked immunosorbent assay (ELISA) and surface plasmon resonance (SPR). Using a peptide library, we mapped epitopes recognized by a given mAb. Finally, we assessed the applicability of these mAbs to routine experimental setups, including Western blotting, immunohistochemistry, and flow cytometry. RESULTS ELISA and SPR analyses revealed that mAbs J591, J415, D2B, 107‐1A4, GCP‐05, and 2G7 bind preferentially to GCPII in native form, while mAbs YPSMA‐1, YPSMA‐2, GCP‐02, GCP‐04, and 3E6 bind solely to denatured GCPII. mAbs 24.4E6 and 7E11‐C5.3 recognize both forms of GCPII. Additionally, we determined that GCP‐02 and 3E6 cross‐react with mouse GCPII, while GCP‐04 recognizes GCPII and GCPIII proteins from both human and mouse. CONCLUSION This comparative analysis provides the first detailed quantitative characterization of the most commonly used mAbs against GCPII and can serve as a guideline for the scientific community to use them in a proper and efficient way. Prostate 74: 1674–1690, 2014. © 2014 Wiley Periodicals, Inc.